The Relationship between Spiritual Intelligence and Work Satisfaction among Leaders and Employees - Koražija Maja; Šarotar Žižek Simona; Mumel Damijan (Naše gospodarstvo/Our economy, 2016)
This study aims to investigate the relationship between spiritual intelligence and work satisfaction among both leaders and employees. Most studies in this area have focused on researching the relationship between employees’ spiritual intelligence and work satisfaction, so we also researched the relationship between leaders’ spiritual intelligence and work satisfaction. Our leading thesis was that leaders and employees with a higher level of spiritual intelligence have a higher level of work satisfaction. In our study, we found no significant relationship between spiritual intelligence and work satisfaction for leaders, but we found a significant positive relationship between spiritual intelligence and workplace satisfaction for employees.